South-South labour internationalism: SIGTUR and the challenges to the status quo - Dobrusin, Bruno Nicolas (2014)
Labor internationalism and solidarity has been dominated historically by the European trade union movement. The 2008 economic crisis and the rise of emerging economies have led to a gradual reorientation of labor relations, increasing the capacity of a group of southern trade unions to influence transnational labor solidarity. This article reviews the increasing connectivity between southern trade unions, with a focus on the Southern Initiative on Globalisation and Trade Union Rights (SIGTUR), which groups confederations from the Global South, with leading unions from Brazil, Argentina, Korea, South Africa, and Australia, among others. The leading argument is that despite shortcomings, SIGTUR has the potential to revitalize labor internationalism through extending the network into articulated global actions that challenge dominant neoliberal globalization.